Association between dietary fiber intake and post-stroke depression among US women: insights from the NHANES 2005–2018 cross-sectional study - Jian, Xueshan; Jian, Shuyang; Zhang, Zhiru; Ye, Yuxuan; Tang, Xiaona; Huang, Rucheng (Frontiers in Nutrition, 2025)
BackgroundFew studies have established a link between the dietary fiber intake (DFI) and post-stroke depression (PSD). Drawing on data collected in the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2018, this investigation systematically examined the association between DFI and PSD in US women.MethodsA cross-sectional study was conducted using data from female participants in the NHANES from 2005 to 2018. The inclusion criteria comprised complete data on DFI, stroke history, and depression status. Multivariate logistic regression models were utilized to evaluate the association between DFI and the risk of PSD among the female population. To assess model validity, the Hosmer-Lemeshow test was performed to examine calibration, and a receiver operating characteristic (ROC) curve was constructed to measure discriminative ability. A restricted cubic spline (RCS) was employed to examine the correlations. Furthermore, subgroup analyses and interactions were also conducted to evaluate the stability of the relationship between DFI and PSD among different subgroups.ResultsAmong 13,143 screened female participants, 105 were diagnosed with PSD. The multivariate logistic regression model, after adjusting for all potential covariates, demonstrated that the odds ratio (OR) for the association between DFI and PSD was 0.92 [95% confidence interval (CI): 0.88–0.96; p < 0.001]. Model calibration was confirmed by the Hosmer-Lemeshow test (p = 0.549), and the area under the receiver operating characteristic curve (AUC) was 0.813 (95% CI: 0.775–0.852), indicating good model fit and strong discriminative ability. In the adjusted Model 3, when DFI was divided into quartiles, participants in the fourth quartile (Q4) exhibited a 70% lower risk of PSD compared to those in the first quartile (Q1) (OR: 0.30, 95% CI: 0.14–0.61; p = 0.001). The RCS analysis indicated an inverse association between DFI and the risk of PSD (p for non-linearity = 0.026). Subgroup analysis revealed that, except for subgroups stratified by age and body mass index (p < 0.05), there were no significant interactions between DFI and other specific subgroups (all interactions p > 0.05).ConclusionThe findings suggest a non-linear negative association between DFI and PSD risk among US women.